Features of exciton migration in pseudoisocyanine J-aggregates - Sorokin, A.V.; Fylymonova, I.I.; Pereverzev, N.V.; Yefimova, S.L. (Functional Materials, 2012)
Exciton migration in pseudoisocyanine (PIC) J-aggregates has been studied via luminescence quenching by an exciton trap. It has been shown that in PIC J-aggregates excitons migrate by coherent mechanism. Exciton diffusion coefficient and diffusion length have been obtained using classical approach developed for molecular crystals. Both of them are much smaller in comparison with exciton diffusion parameters for molecular crystals.